Telling Tales of Oppression and Dysfunction: Narratives of Class Identity Reformation - Hurst, Allison L. (Qualitative Sociology Review, 2007)
I compare experiences and class identity formation of working-class college students in college. I find that all working-class students experience college as culturally different from their home cultures and have different understandings and interpretations of this difference based on race, class, and gender positions. I find that students develop fundamentally different strategies for navigating these cultural differences based on the strength or weakness of their structural understandings of class and inequality in US society. Students with strong structural understandings develop Loyalist strategies by which they retain close ties to their home culture. Students with more individual understandings of poverty and inequality develop Renegade strategies by which they actively seek immersion in the middleclass culture of the college. These strategic orientations are logical responses to the classed nature of our educational system and have very significant implications for the value and experience of social mobility in an allegedly meritocratic society.